PROSPECTS FOR THE DEVELOPMENT OF ELECTRONIC PUBLIC PROCUREMENT IN UKRAINE - NAHAICHUK, Viktoriia; HAVRYSH, Natalya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article is devoted to the study of the general state of functioning of electronic procurement in Ukraine in modern conditions, the toolkit of the electronic procurement analysis module in the Prozorro system and, in particular, the changes that occurred after the introduction of martial law. The essence of the concept of public procurement and the prerequisites for their occurrence are revealed. Public procurement is a huge market and a huge responsibility for the state. The market, which should provide free access to all state customers and any suppliers to open and transparent auctions. The state is one of the main participants in the economic process as a consumer of goods, works and services. Public procurement makes up a significant part of world trade flows, which can roughly reach 1 trillion euros per year. The success of the economy depends on the effectiveness of public procurement. The world experience of the implementation of public procurement and its influence on the implementation of this system in Ukraine were studied. It is difficult to imagine the development of the country’s economy without a fully functioning transparent public procurement mechanism capable of ensuring seamless interaction between all representatives of the economic system. Prospects for the development of e-procurement in Ukraine were considered, existing problems were identified and ways to solve them were proposed. the use of electronic tools in public procurement offers a number of important advantages, such as: significant savings for all parties, simplified and shortened processes, reduced bureaucracy, transparency, more innovation, new opportunities for business by improving the access of enterprises, including small ones and medium-sized enterprises to public procurement markets. The system has been actively developing, and with the transition of Ukraine to a state of war, this process deepened and accelerated. Long-term plans for improving the work and developing strategies for Ukraine during the war and post-war period, for its reconstruction with the involvement of foreign investments and donor funds have been outlined.